Is Probability an Empirical Term in Frequency Interpretation? - Nekrašas, Evaldas (Problemos, 1970)
R. von Mises claiming that frequency theory of probability is empirical proceeded from the possibility of reducing theoretical terms to empirical ones. The paper asserts, on the basis of analysed relation between frequency interpretation of probability and reductionist program, that explicit definition of probability not only does complicate theory but does not establish the desired connection between theory and empirical reality. Empirical elements in frequency interpretation of probability are not independent, therefore probability is not an empirical term in this interpretation.